Learning Theory: Constructivism Theories and The Implications for Arabic Language Teaching - Abdul Muid; Aminah, Aminah (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
This study aims to analyse constructivism's theory and its implications for Arabic language learning. This study departs from the assumption that there is no perfect theory in learning. All theories have advantages and disadvantages, and the idea of applying these theories in learning Arabic is the right step for language teachers, especially Arabic to realise the goals that have been set. This research uses a qualitative approach with the type of literature (library research) where the author seeks to collect data related to the theory of learning constructivism in Arabic language learning through books, scientific journals, seminar proceedings, previous studies, and other scientific writings. This stage is used to increase the flexibility of the offer of the constructivist language learning theory in Arabic language learning. The results of the study show that the theory of constructivism focuses on the practical application of language through conversation simulation and real problem-solving. Students are engaged in activities that are close to real-life situations, such as role-playing, to functionally apply Arabic, creating a well-rounded and holistic approach to learning Arabic.